The effect of celebrity endorsement and customer review on purchase interest with brand image as a mediating variable at e-commerce Shopee - Ilvi Nur Widiana; Muhafidhah Novie (Institute of Computer Science (IOCS), 2024)
This study aims to determine the effect of celebrity endorsement and customer reviews on buying interest with brand image as a mediating variable in shopee e-commerce. This type of research is quantitative with a descriptive approach. The research sample was 100 respondents. Data collection techniques using questionnaires. Data analysis techniques using path analysis. The results showed that 1) celebrity endorsment has a positive but insignificant effect on buying interest. 2) celebrity endorsment has a positive and significant effect on brand image.3) customer review has a positive and significant effect on purchase intention.4) customer review has a positive and significant effect on brand image.5) brand image has a positive and significant effect on purchase intention